2017
DOI: 10.1038/s41598-017-11842-5
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid induces apoptosis and autophagy in the treatment of Tongue Squamous cell carcinomas

Abstract: Oleic acid (OA), a main ingredient of Brucea javanica oil (BJO), is widely known to have anticancer effects in many tumors. In this study, we investigated the anticancer effect of OA and its mechanism in tongue squamous cell carcinoma (TSCC). We found that OA effectively inhibited TSCC cell proliferation in a dose- and time-dependent manner. OA treatment in TSCC significantly induced cell cycle G0/G1 arrest, increased the proportion of apoptotic cells, decreased the expression of CyclinD1 and Bcl-2, and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 44 publications
11
69
0
Order By: Relevance
“…Conversely, Miller et al () suggested that the growth‐inhibitory effects of milk fat on SW480 and MCF‐7 cells could be in part related to the high levels of OLA present in milk fat. Although some studies found that OLA at low concentrations (<50 μM) could promote the proliferation of cancer cells (Falconer et al, ; Nano et al, ), higher concentrations of OLA (>100 μM) have been shown to have potent anticancer effects by inducing cell cycle G0/G1 arrest, apoptosis, and autophagy in cancer cells (Fernanda Cury‐Boaventura et al, ; Jiang et al, ). In the present study, the effective dose of low‐BHI SCF (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Miller et al () suggested that the growth‐inhibitory effects of milk fat on SW480 and MCF‐7 cells could be in part related to the high levels of OLA present in milk fat. Although some studies found that OLA at low concentrations (<50 μM) could promote the proliferation of cancer cells (Falconer et al, ; Nano et al, ), higher concentrations of OLA (>100 μM) have been shown to have potent anticancer effects by inducing cell cycle G0/G1 arrest, apoptosis, and autophagy in cancer cells (Fernanda Cury‐Boaventura et al, ; Jiang et al, ). In the present study, the effective dose of low‐BHI SCF (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…All the evidence indicated that OA could elicit an induction of a process related to autophagy by the Akt/mTOR pathway. Moreover, a growth rate of inhibition of 58% (after 40 days of treatment with 4 mg of 48 ) was demonstrated in an in vivo assay on xenograft nude mice expressing OSCC cells . In an interesting paper, the synergistic effect of Gambogic acid ( 49 ) with RT was investigated.…”
Section: Autophagy Modulators In Oscc and Esccmentioning
confidence: 99%
“…Up-regulation of macrolipophagy was first detected in hepatocytes exposed to high levels of oleic acid (22). Subsequent studies showed that lipid overload can increase autophagy in cells including neurons, beta cells, myocytes and epithelial cells (6670). Conversely, blocking autophagy in cultured myocytes leads to elevated TG levels and cell death as a result of lipid overload (71).…”
Section: Functions Of Lipophagymentioning
confidence: 99%